Relationship Between Peripheral Refraction in Different Retinal Regions and Myopia Development of Young Chinese People - Zheng, Xiangyue; Cheng, Dejin; Lu, Xiaoli; Yu, Xiaoyi; Huang, Yuting; Xia, Yujie; Lin, Chuni; Wang, Zhao (Frontiers in Medicine, 2022)
Objective: To observe associations between regional peripheral refraction and myopia development in young Chinese people. Methods: Two hundred and forty-one young adult subjects (21 emmetropes, 88 low myopes, 94 moderate myopes, 38 high myopes) aged 18-28 years were included, and only right eyes were tested. Eye biometrics were measured before pupil dilation using Lenstar. Relative peripheral refractive errors (RPRE) were measured after pupil dilation using multispectral refractive topography (MRT), at nine retinal eccentricities: 0 to 5 degrees, 5 to 10 degrees, 10 to 15 degrees, 15 to 20 degrees, 20 to 25 degrees, 25 to 30 degrees, 30 to 35 degrees, 35 to 40 degrees, and 40 to 45 degrees. Results: In this study, RPRE increased with eccentricity and it shows a growing trend with the increase of degree of myopia among emmetropia, low myopia and moderate myopia groups, and RPRE varied with myopia severity at eccentricities between 20 and 35 degrees only. In addition, axial length (AL) and RPRE were positively correlated between 20 and 45 degrees, and AL was an independent risk factor for RPRE between 20 and 35 degrees. Conclusion: These findings indicate that at eccentricities between 20 and 35 degrees RPRE may be closely related to refractive development and eye growth in young Chinese people.